(3GdhSjW aj TQM GdJTQjYGJ GdJLGQjI (B:s (3GdCYeGd GdJLGQjI(B-(3GdYbhO GdJLGQjI(B-(3GdJLGQ(B-(3GdeJLQ (B= The mediator in explaining the commercial law : business-commercial contracts-traders-store /s - (3GdYcjdj, YRjRs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2017)
(3jJMOK gPG GdcJGH Yf OQGSI GdCMcGe GdJj hQOJ aj GdJTQjYGJ GdJLGQjI hGdeJYdbI HGdCYeGd GdJLGQjI hGdJLGQ hGdeJLQ hGdYbhO GdJLGQjI hGdYedjGJ GdeUQajI hGdTQcGJ GdJLGQjI hGdChQGb GdJLGQjI JbJVjfG Cf fegO dgG HebOeI YGeI fdbj ajgG fXQI TGedI Ydi GdbGfhf GdJLGQj fhVM ajgG GdebUhO Hg hHjGf ehbYg ef GdJbSje GdYGe ddbGfhf Ke fMOO fWGb JWHjbg ceG jHMK aj gPg GdebOeI NUGFU GdbGfhf GdJLGQj hGSJbdGdg Yf GdbGfhf GdeOfj hGdeUGOQ GdJj JfJL YfgG hJJhdO efgG GdbhGYO GdJj jTJed YdjgG(B.s
(3HHdjhLQGajI (B: (3UaMI (B411-416.s
Keywords: (3GdChQGb GdJLGQjIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3GdYbhO GdJLGQjIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3GdbGfhf GdJLGQjs -- (3GdCQOfs